2022
DOI: 10.1002/jemt.24039
|View full text |Cite
|
Sign up to set email alerts
|

PET‐CT versus MRI in the diagnosis of lymph node metastasis of cervical cancer: A meta‐analysis

Abstract: To compare the clinical application value of positron emission tomography–computed tomography (PET‐CT) and magnetic resonance imaging (MRI) in the diagnosis of cervical cancer lymph node metastasis. We searched PubMed and other databases for the studies comparing the use of PET‐CT and MRI for the diagnosis of cervical cancer lymph node metastasis up to January 20, 2021. We strictly followed the inclusion and exclusion criteria to screen the literature and extract the data. Quality Assessment of Diagnostic Accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Sensitivities of 64% to 93% for presurgical magnetic resonance imaging (MRI) and of 66% to 85% for presurgical computed tomography (CT) have been reported in the detection of cervical lymph node metastasis [ 4 ]. Although, in a meta-analysis from Sun et al, 2022, better sensitivity and specificity was found for the MRI than the CT [ 5 ], other studies show similar sensitivity rates for both MRI and CT [ 6 ]. Relatively high sensitivity (75% to 90%) and specificity (94% to 99%) are reported in detecting lymph node metastases with 8F-fluorodeoxyglucose positron emission tomography (18FDG-PET) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivities of 64% to 93% for presurgical magnetic resonance imaging (MRI) and of 66% to 85% for presurgical computed tomography (CT) have been reported in the detection of cervical lymph node metastasis [ 4 ]. Although, in a meta-analysis from Sun et al, 2022, better sensitivity and specificity was found for the MRI than the CT [ 5 ], other studies show similar sensitivity rates for both MRI and CT [ 6 ]. Relatively high sensitivity (75% to 90%) and specificity (94% to 99%) are reported in detecting lymph node metastases with 8F-fluorodeoxyglucose positron emission tomography (18FDG-PET) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of PET, Sironi et al have reported that PET/CT provided sensitivity of 100% and speci city of 99.6% for the detection of lymph nodes metastases larger than even 0.5 cm in diameter 24 . A recent meta-analysis has shown that CT, MRI, and PET performed comparably for assessing nodal metastasis, with low sensitivity but high speci city 7 , although integrated PET/CT demonstrated higher sensitivity and comparable speci city to MRI and CT 6,25 . Moreover, the new PET modality of 18 F-FDG PET/MRI, which has the combined features of high softtissue contrast along with functional imaging of FDG uptake, may also have high diagnostic value in cervical cancer and potentially better diagnostic performance compared with the conventional imaging modalities of CT, MRI, and PET/CT 12,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of 18 F-FDG PET, Sironi et al have reported that 18 F-FDG PET/CT provided sensitivity of 100% and specificity of 99.6% for the detection of lymph nodes metastases larger than even 0.5 cm in diameter 24 . A recent meta-analysis has shown that CT, MRI, and 18 F-FDG PET performed comparably for assessing nodal metastasis, with low sensitivity but high specificity 7 , although integrated 18 F-FDG PET/CT demonstrated higher sensitivity and comparable specificity to MRI and CT 6 , 25 . Moreover, the new PET modality of 18 F-FDG PET/MRI, which has the combined features of high soft-tissue contrast along with functional imaging of 18 F-FDG uptake, may also have high diagnostic value in cervical cancer and potentially better diagnostic performance compared with the conventional imaging modalities of CT, MRI, and 18 F-FDG PET/CT 12 , 14 .…”
Section: Discussionmentioning
confidence: 99%